2014
DOI: 10.1590/0100-2945-413/13
|View full text |Cite
|
Sign up to set email alerts
|

Análise de distância genética entre acessos do gênero Psidium via marcadores ISSR

Abstract: analYsis of Genetic distance Between access of the Gender Psidium BY ROUTE MARKERS ISSRaBstract-The objective of this study was to evaluate the genetic distance among 37 accessions of cultivated species Psidium guajava, L. (guava) and Araçás to the genus Psidium to the germplasm colection of the Universidade Estadual Norte Fluminense (UENF) by ISSR molecular markers. In the 17 selected markers, 216 polymorphic bands were obtained. By UPGMA method there was the formation of five main clusters. Accessions of ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…The affinity between P. guajava and P. guineense is corroborated in the work of Oliveira et al (2014), who verified greater genetic proximity between P. guajava and P. guineense, when evaluating the genetic divergence between accesses of the genus Psidium, via molecular markers.…”
Section: Resultsmentioning
confidence: 67%
“…The affinity between P. guajava and P. guineense is corroborated in the work of Oliveira et al (2014), who verified greater genetic proximity between P. guajava and P. guineense, when evaluating the genetic divergence between accesses of the genus Psidium, via molecular markers.…”
Section: Resultsmentioning
confidence: 67%
“…Sitther et al (2014) reported the formation of six groups composed of eight accessions of P. guajava, including three species of wild Psidium accessions of P. friedrichsthalianum, P. guineense, and P. sartorianum in the United States germplasm. Oliveira et al (2014) found greater proximity of P. cattleianum with guava accessions. However, these species possess proven differences concerning evolutionary distance in relation to guava, mainly because it is polyploid, being evidenced different ploidy levels, such as tetraploid, heptaploide, or octaploide (Costa et al, 2008;Ray, 2002;Singh and Sehgal, 1980;Hirano, 1967).…”
Section: Similarity Genetic Based On Dendrogram Of Jaccard Coefficientmentioning
confidence: 86%
“…Through research developed with other species of the same family, it was possible to detect the presence of variability regarding the amount of polymorphic fragments amplified. Oliveira et al (2014), evaluating the genetic distance among 37 accesses of Psidium spp., using 17 primers, obtained 216 polymorphic fragments, with an average of 13 by primer. Studying the diversity of 272 genotypes of the same species of the jaboticabeira family, Myrcia splendens (SW), Brandão et al (2011) used 10 primers and identified 70 polymorphic fragments.…”
Section: Polymorphism and Discriminatory Power Of Issr Primersmentioning
confidence: 99%
“…Thus, this marker has been widely used as a supporting tool in breeding programs to characterize and access the genetic variability of several species (DIAS et al, 2015;OLADOSU et al, 2015;OLIVEIRA et al, 2014).…”
Section: Introductionmentioning
confidence: 99%